Epidemiology of injury due to race-day jockey falls in professional flat and jump horse racing in Ireland, 2011-2015 - O'Connor, S.; Warrington, G.; McGoldrick, A.; Cullen, S. J. (Journal of Athletic Training, 2017)
Context: Professional horse racing is considered a high-risk sport, yet the last analysis of fall and injury incidence in this sport in Ireland was completed between 1999 and 2006.